RESILIENSI ORANG TUA TERHADAP ANAK DENGAN HAMBATAN INTLEKTUAL DI SLB BINA SIWI BANTUL - Aqil Zayyan, Muhammad; Sukadari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Parents of children with intellectual disabilities encounter various psychological, social, and economic challenges throughout the parenting process. These challenges often lead to emotional stress, concerns regarding their children's future, and increased caregiving demands. Therefore, resilience plays a significant role in enabling parents to adapt positively to these circumstances. This study aimed to describe the resilience of parents who have children with intellectual disabilities at SLB Bina Siwi Bantul. The study employed a qualitative descriptive approach involving five parents selected through purposive sampling. Data were collected using participant observation, structured interviews, and documentation. The credibility of the data was ensured through source and technique triangulation, while the analysis followed the Miles and Huberman interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that parental resilience is reflected through self-acceptance, emotional regulation, optimism, self-efficacy, social support, impulse control, and the ability to analyze the causes of problems. Parents gradually accepted their children's conditions, managed emotional challenges, maintained positive expectations for their children's future, sought appropriate interventions, and received support from family, schools, and surrounding communities. These findings suggest that resilience develops through continuous adaptation supported by internal strengths and external social resources, enabling parents to provide positive parenting and support their children's optimal development.